The mediating role of resilience in the relationship between social support and posttraumatic growth among colorectal cancer survivors with permanent intestinal ostomies: A structural equation model analysis. (August 2017) - Dong, Xiaoling; Li, Guopeng; Liu, Chunlei; Kong, Linghua; Fang, Yueyan; Kang, Xiaofei; Li, Ping
Abstract: Purpose: Information on posttraumatic growth (PTG) among colorectal cancer (CRC) survivors with permanent intestinal ostomies is limited. The aim of this cross-sectional study was to investigate the occurrence of PTG among CRC survivors with permanent intestinal ostomies and its association with perceived social support and resilience. Methods: This study was conducted with 164 CRC survivors with permanent intestinal ostomies at least one month after surgery. Participants completed questionnaires assessing socio-demographic and clinical characteristics, perceived social support, resilience and PTG. Results: The mean total score on the Post Traumatic Growth Inventory was 66.74 (SD = 13.99). Perceived social support (r = 0.450) and resilience (r = 0.545) were significantly positively correlated with PTG. Structural equation modeling analysis showed that resilience mediated the relationship between perceived social support and PTG in which the indirect effect of perceived social support on PTG through resilience was 0.203 (P < 0.001). Conclusions: Moderate to high PTG was found in CRC survivors with permanent intestinal ostomies. The most important implication of this study was that improving social support and resilience might be scientific intervention strategies for promoting PTG among CRC survivors. Highlights: Moderate to high PTG in CRC survivors with permanent intestinal ostomies. Resilience and perceived social support positively associated with PTG. The mediating role of resilience between perceived social support and PTG.